Inheritance of low erucic acid in Indian mustard [Brassica juncea (L.) Czern. and Coss.] - Singh, Jai; Yadava, Devendra K.; Vasudev, Sujata; Singh, Navven; Muthusamy, Vignesh; Prabhu, Kumble V. (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetics of erucic acid content was studied using six generations viz., P1, P2, F1, F2, B1 and B2 derived from the crosses,Varuna × LES-39 andVaruna × LES-1-27.The trait high erucic acid content was partially dominant over low erucic acid content in both the crosses. In both the crosses, adequacy of additive – dominance model suggested absence of non-allelic interactions.The study revealed that selection for low erucic acid would result in isolation of plants with high oleic and linoleic acids and hence, it should be possible to develop high oleic acid lines having low erucic acid content in mustard.